2018
DOI: 10.1111/jfpp.13689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on yield extract and antioxidant activity of peanut skin using modified supercritical carbon dioxide and soxhlet extraction

Abstract: Theobjectiveofthisstudywastostudyandcomparetheeffectofparticlesizeon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Small particle size can cause solute re‐adsorb on matrix surfaces leads to the inhomogeneous extraction process (Sodeifian et al., 2018). The use of small particle size also leads to the formation of hard lumps when in contact with the solvent caused the sample's compaction in the extraction vessel consequently it would slow down solute mass transfer rate and reduced solvent ability to attract the solute (Putra et al., 2018). Even though bigger particle size provides less surface area per volume, this study applied the soaking method at the beginning of the extraction process thus rendered swelling phenomena which reduced the solute viscosity and increased available surface area of the particle; hence encourage mass transfer from the solid to fluid phase leads to increasing extraction yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small particle size can cause solute re‐adsorb on matrix surfaces leads to the inhomogeneous extraction process (Sodeifian et al., 2018). The use of small particle size also leads to the formation of hard lumps when in contact with the solvent caused the sample's compaction in the extraction vessel consequently it would slow down solute mass transfer rate and reduced solvent ability to attract the solute (Putra et al., 2018). Even though bigger particle size provides less surface area per volume, this study applied the soaking method at the beginning of the extraction process thus rendered swelling phenomena which reduced the solute viscosity and increased available surface area of the particle; hence encourage mass transfer from the solid to fluid phase leads to increasing extraction yield.…”
Section: Resultsmentioning
confidence: 99%
“…SFE also applicable for the separation of heat‐labile compounds since the system is operate at moderate temperature and pressure. In other studies, SFE is proven to give better quality of desired constituents even though the yield is lower than conventional solvent extraction (Peng et al., 2020; Putra et al., 2018). Besides, the properties of supercritical fluid, higher diffusivity and lower density, surface tension, and viscosity, can be altered by manipulating the operating conditions (pressure and temperature), which provide more effective extraction process (Lee et al., 2013; Putra, Rizkiyah, Idham, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, pure CO 2 is not an appropriate extraction fluid for polar analytes and ethanol is needed to enhance the polarity of supercritical carbon dioxide. Previous studies have shown that SC-CO 2 extraction gives a low amount of yield as compared with Soxhlet extraction (Putra et al 2018) . What is more, SFE were fewer used for high quality hemp oil and other edible oils mainly due to very high investment costs of SFE equipment.…”
Section: Introductionmentioning
confidence: 97%
“…As some researchers reported, the antioxidant potential of plant oils was mainly attributed to polyunsaturated fatty acids, vitamin E homologues (e.g. tocopherols)(Ramadan et al2006;Putra et al 2018). In vegetable oils, tocopherols are the most important natural antioxidants present(Kamal-Eldin et al1996).…”
mentioning
confidence: 99%
“…Peanut skin contains flavonoid and phenolic compounds that they retard oxidative degradation of lipids and thereby improve the quality and nutritional value of food. Peanut skin extract commonly can be anti‐allergenic, antiviral, anti‐inflammatory, anticarcinogenic activities, and also prevention of cancers (Chanda, Bhayani, & Desai, 2013; Elsorady & Ali, 2018; Putra, Rizkiyah, et al., 2018; Putra, Yunus, Ruslan, Idham, & Idrus, 2018).…”
Section: Introductionmentioning
confidence: 99%